Identifikasi Kondisi Hutan Lindung Pulau Sebatik Kabupaten Nunukan Kalimantan Utara - Husmul Beze; Suparjo (Poltanesa, 2019)
In the last ten years the people on Sebatik Island have experienced water shortages. This happened because the forest which is the source of community water dried up. It is estimated that the drying up of these springs is due to changes in the function of forests as water reserves. This change in forest function occurs as a result of the process of clearing forests for plantations or other development activities. This is why it is necessary to analyze the protected forest cover on Sebatik Island. In this study, analysis of forest cover was carried out based on Landsat satellite imagery. To check the correctness of the analysis results on the satellite image, field checks are carried out. Based on the research results, the forest area on Sebatik Island has an area of ​​2,088.37 ha. The damaged forest is estimated to be 339.97ha, while the protected forest area which is still in good condition has an area of ​​1,748.40 ha.